(untitled) (Proceedings of the International Conference on Public Health, 2022)
In many countries’ majority of the national health workforce is made up of nurses thus they play a major role in health care delivery. Burnout is a physical or psychological fatigue or exhaustion felt by an individual due to personal, work and client related stressors. Previous studies report that nurses, especially psychiatric nurses are more prone to burnout which may adversely affect service delivery. Objective of the study was to determine the level of burnout among psychiatric nurses in National Institute of Mental Health Sri Lanka. A descriptive cross-sectional study was conducted among all nurses involved in patient care (n=346) working at National Institute of Mental Health, Sri Lanka. The study instrument was a self-administered questionnaire. Burnout was measured using the translated and validated Copenhagen Burnout Inventory (CBI). Cut off value of overall burnout was taken as 40.16 points according to the validation study. Response rate was 85%(n=296). Prevalence of burnout was 31.8% (95% CI of 30.5% - 33.55%). Adjusted prevalence was 27.1% when considering the Positive predictive value/sensitivity of CBI. Highest mean score was seen in Personal burnout which was 40.75(+18.76 SD) with a 95% CI of 38.60-42.90. Work related burnout had a mean score of 29.24(+17.76SD) with a 95% CI of 27.22-31.28. Client related burnout was 29.53(+16.97SD) with a confidence interval of 27.59-31.47. Total burnout score was 33.25 (+of 15 SD) with a confidence interval of 31.53-34.96. In conclusion, Burnout affects more than one third of nurses at NIMH. Personal burnout score was significantly higher than the means of work related or client related burnout scores. It is a responsibility of health managers to address this problem before it compromises patient care at NIMH.